(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to the issues of social adjustment of military training cadets. The process of socio-pedagogical adaptation of cadets in the conditions of a military educational institution is a pedagogical system that plays an important role for effective functioning and development in certain conditions. Many scientists express social adaptation as a system aimed at mastering new social relations. It does not destroy the biological forms of adaptation, but transforms and mediates them, containing them as an internal element that regulates and transforms them.